2021
DOI: 10.3390/toxics9020032
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Combined Inhalation Exposure Scenarios to Biocidal Mixtures: Biocidal and Household Chemical Products in South Korea

Abstract: Global regulations of biocides have been continuously enhanced for protecting human health and the environment from potentially harmful biocidal products. Such regulations consider the combined toxicity caused by mixture components in a biocidal product of which approval and authorization are to be enhanced. Although the combined exposure scenarios of components in mixtures are firstly needed to conduct the mixture risk assessment, systematic combined exposure scenarios are still lacking. In this study, combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…According to a recent study, cetylpyridinium chloride showed a potential to induce apoptosis in human lung cells [41]. However, this binary combination for further experimental studies was not included in a real combined exposure scenario database for household chemical and biocidal products developed in our previous meta-study results [20]. We demonstrated that substances regulating MIEs activated the following KE, according to the AOP.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…According to a recent study, cetylpyridinium chloride showed a potential to induce apoptosis in human lung cells [41]. However, this binary combination for further experimental studies was not included in a real combined exposure scenario database for household chemical and biocidal products developed in our previous meta-study results [20]. We demonstrated that substances regulating MIEs activated the following KE, according to the AOP.…”
Section: Discussionmentioning
confidence: 90%
“…Data Sets 2.1.1. Co-Exposure Biocide Data Collection Our previous meta-study [20], investigated real combined inhalation exposures to biocides including, 1733 real products containing two or more biocides marketed in South Korea. Of the 1733 products, except 130 duplicated combinations, we confirmed 768 combined exposure scenarios.…”
Section: Receptor and Ligand Data Collection For MD And Pharmacophorementioning
confidence: 99%
“…Additionally, previous studies have demonstrated a limited ability to detect health effects due to low-level chronic exposure and periodic high-level exposure among humans who mix, load, and apply pesticides [ 58 , 59 ]. An additional probable explanation might be that a questionnaire, as an indirect exposure assessment method, may not accurately reflect the situation may not provide an objective response to health effects ( Supplementary Material ) [ 16 ]. Thus, information obtained from research subjects in a survey on health impacts might be inaccurate due to reporting bias, which can be predicted as an underestimation [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Global regulations have been improved in recent years to protect human health and the environment from potentially harmful biocide products [ 16 ]. The European Union (EU) Biocide Product Regulation (BPR) and the Korea Household Chemicals and Biocide Safety Act (KBPR) were enacted to continuously improve and supplement the safe management of biocidal products [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since August 2011, the pulmonary toxicity of biocidal agents, which may lead to severe lung injury, has emerged as a critical issue in South Korea . The presence of small amounts of biocides in humidifier disinfectants may lead pulmonary fibrosis, which has affected 7685 people and resulted in 1751 deaths, according to data published in March 2022 . Consequently, it is necessary to detect and identify biocidal agents in different products to reduce or eliminate the risk of injury or death.…”
Section: Introductionmentioning
confidence: 99%